The Age of Majority in Islamic Law and the Pakistani Legal System: An Overview - Amr Ibn Munir (Journal of Religion and Society, 2026)
Underaged marriages are one of Pakistan’s biggest banes today. Minors entering into marriages is an unfortunate scenario but a harsh reality. Under Islamic law, in order for one to enter into any sort of legal relationship, one must have ahliyyah (the legal capacity) to do so. A person is presumed to have ahliyyah when he reaches the age of majority. The Qur’an and the Sunnah have not specifically stipulated an age of majority, while one Companion and the Muslim jurists have stipulated different ages of majority. A person is presumed to have attained the age of majority when he attains puberty or physical maturity. However, this is only one requirement, there is a major requirement of mental maturity as well, otherwise one cannot become a major. In Pakistan, previously, the law did not provide a uniform age of majority and provides separate ages for both male and female. The Pakistani Superior Courts have also at first considered only physical maturity as the major criteria in underaged marriage cases before venturing into the added prerequisite of mental maturity as well. One Court has even recommended raising the age of girls to 18 by the legislature and has declared such a law to be Islamic. This was eventually done in 2025 where the ages of both genders have been uniformly declared to be 18 years. While this is a welcome development, owing to the socio-economic conditions of Pakistan, such legislation must also come with certain exceptions for marriages under 18 years of age such as cases of poor or orphaned girls with an added stipulation of education being provided by the boy who wishes to enter into marriage with her or his family as the case may be. The methodology used in this paper is doctrinal. Keywords: Age of Majority, Age of Marriage, Ahliyyah, Sabi, Sabi Mumayez.